(untitled) (Forum Agribisnis, 2017)
Indonesia is the third largest world cocoa producer. For years, cocoa bean from Indonesia has been exporter as raw beans. Domestic cocoa manufacturing industry is still dominated by international companies such as Nestle, Marz, JB Cocoa Malaysia, and others than domestic small and medium enterprise. This condition shows that value added of cocoa processing have not yet accepted by local entrepreneurs. Nowadays, most of the small and medium enterprise produce intermediate and compound chocolate products with low use of cocoa butter volume in proportion. Then, those intermediate products would be exported and will be reimported again by Indonesia as final product. Pipiltin Cocoa is the only small-scale natural chocolate producer in Indonesia using local cocoa bean from Bali and Aceh. This research focuses on value added analysis of bar chocolate in Pipiltin Cocoa produce which is important to conduct in order to know the added value made from a domestic small-scale cocoa farm producing original cocoa products.